Survival, Chemotherapy and Chemosensitivity Predicted by CTC Cultured In Vitro of SCLC Patients - Ju, Lixia; Yang, Juan; Zhai, Changyun; Chai, Shuizhen; Dong, Zhiyi; Li, Minghua (Frontiers in Oncology, 2021)
Backgroud: The prognosis for small cell lung cancer (SCLC) patients receiving later-line treatment is very poor and there is still no standard treatments after the second-line setting. Analyzing the susceptibility of chemotherapeutic drugs with circulating tumor cells (CTCs) cultured in vitro may contribute to optimize the therapeutic regimen. However, so far CTCs have been barely used for studying their chemosensitivity due to the lack of technology to obtain wholly intact and viable CTCs. Methods: Based on a retrospective study of the therapeutic response of 99 patients with unresectable SCLC, the CTC count in 14 SCLC patients was detected before and after chemotherapy to evaluate its role as a potential marker of response. Furthermore, the drug susceptibility of CTCs cultured in vitro obtained from ClearCell FX® System was tested and the therapy response was evaluated. Results: All of the 99 patients received the first-line chemotherapy and the objective response rate (ORR) was 74.7%. A total of 36 patients received the second-line therapy and the average duration was 2.6 months, and only 11 cases out of them received the third-line therapy but no one responded. The change of CTC counts was identified to be correlated with therapy response. However all the five SCLC patients who were administered with the drugs according to the drug susceptibility test of CTCs for two cycles underwent progression of disease. Conclusion: The results showed that the responses of chemotherapy are very poor in later lines and the drug susceptibility test using CTCs primary cultured in vitro may not benefit the improvement of therapeutic regimen of SCLC patients.